Promoting adolescent health through integrated human papillomavirus vaccination programs: The experience of Togo. (31st March 2022) - Engel, Danielle; Afeli, Abra Dela Jeanne; Morgan, Christopher; Zeck, Willibald; Ross, David A; Vyankandondera, Joseph; Bloem, Paul; Adjeoda, Kodjovi Robert
Abstract: The introduction of the Human papillomavirus (HPV) vaccine has shown potential to not only prevent cervical cancer but also drive adolescents' access to other health care services, even in low-income countries. Few studies have been conducted to date to identify best practices and estimate the acceptance, operational challenges and benefits of including broader adolescent health interventions into immunization efforts, knowledge which is essential to supporting widespread integration. In this paper we review the efforts undertaken by the government of Togo to integrate adolescent health programming with the HPV vaccination roll out. With the support of partners (GAVI, WHO, UNFPA and UNICEF), the country successfully completed, in 2017, two years of an HPV vaccine demonstration project, which entailed vaccinating 10-year-old girls against HPV in two selected districts of the country and integrating a health education component focused on puberty education / menstrual hygiene and hand washing practice. Our study is a post-implementation program evaluation, using mixed methods to assess key questions of feasibility and acceptability of an integrated adolescent package of care. It showed that the HPV vaccination in conjunction with the health education sessions was well received by the majority of health care providers, teachers and parents. Our study confirmed that in Togo it proved feasible to combine education and HPV vaccination in school-based service delivery. However, more operational research is neded to understand how to increase the impact and sustainability of the co-delivery of interventions. We did not analyze the health impact and cost implications of the intervention, which will be an important consideration for scaling up such integration efforts alongside routine immunization.